Desvelando a atuação da enfermeira docente no estágio supervisionado em enfermagem: análise dos saberes docentes e práticas pedagógicas - Silva, Silvana Rodrigues da (2014)
This paper approaches the activity of nursing professors in the college discipline of Internship on Nursing. Nowadays, this level of teaching demonstrates an extension policy from graduation courses, which have been associated to new work requirements for the professionals of the field. Specifically in the health area there still is a resistance to change, as we evidenced little reflection on education and on the teaching knowledge of the nurses. These professionals usually don t choose the pedagogical practice as guide to teaching. The goal of this paper was to analyze the teaching knowledge that permeates the practices adopted by egress nursing professors from a nursing bachelor\'s degree from a public university in Amapá and that teach the discipline Internship on Nursing. Our theoretical framework is anchored in authors that have researches on Internship on Nursing, among them are Fazenda and Piconez (1991), Brzezinski (1996), Pimenta and Lima (2009), and on Nursing are Alves (2000), Backes (2000), Ito (2005), Costa (2008). In the subject of knowledge and professionalization of teaching, we based ourselves on Gauthier et al. (1998), Guimarães (2006) and Tardif (2010). This paper was based on qualitative approach and in order to achieve its objectives, we selected three methodological resources: a questionnaire, observation without interaction and semi-structured interviews. We also used the analysis of documents. There were 24 participants that met the requirements to be in the study and answered the questionnaire. From these 24 individuals, four teachers were selected and their classes were observed from September, 2012 to June, 2013. The observations happened in the city of Macapá, Brazil, and the acting scenery of the participants was the basic health unities. Semi-structured interviews were made with the professors after the period of observation. The triangulation of data and the analysis of content by Laurence Bardin were used as technical analysis of information. The analyses were based on two parameters: the teaching knowledge in the area of Internship on Nursing and, strengths and weaknesses in pedagogical practices in Internship on Nursing. It was evidenced from the teaching knowledge that the approach of these professionals surface with innovative attitudes in an attempt to overcome the traditional training. As strengths, through dialogue we highlighted the empathy towards students and professionals, how experience reports and the use of regional idioms strengthened reception, made the community closer and dribbled the conflicts arisen in these scenarios. The weaknesses are evidenced in the distancing of educational institutions and services, aggravated by curricular fragmentation, and overcrowding in the areas of internship. Our thesis is realized by recognizing that the pedagogical knowledge emerge as the teacher develops their practice, ie the everyday of the profession has a strong influence for the development of this knowledge and not only the knowledge from the academy. In this sense, we understand that we cannot discuss the teaching knowledge in an isolated form, without taking into account all the complexity that involves the process of teaching and learning as well as the various contexts, social interactions, institutions involved, the resources available; ultimately, the various integrated knowledge.